Modifikasi Unit Pembersih Gabah Mesin Mini Combine Harvester Tipe Mcb-120 - Ariadi Widiantoni; Andriyono Andriyono; Yosefina Mangera (Faculty of Agriculture, Musamus University, 2019)
This study aims to get cleaner grain yields by installing filters and removing the wind regulating valves on the MCB 120 mini combine harvester blower. The procedure in this study consists of the first step which involves the preparation, supply of tools, materials and design of the ingredients, the second stage is the manufacture of tool, and the third stage is observation (the level of cleanliness of grain before and after using the sarong and recapitulation of tool making). Dirt mixed with grain can be reduced after cleaning using a sieve, which is 15.7% (after using a sieve) on the observation of cyclical varieties, then for cigelis variety results which is 17.5% (after using a filter).